An investigation into the financial management practices on the performance of Elephant Lodge - Muridzo, Fungisai S. (Midlands State University, 2017)
The study’s intention was to investigate how financial management practices were impacting the operational performance of Elephant Lodge Private Limited. It looked at the overall financial management practices in the Small to Medium Size Enterprises (SME) sector but focusing on Elephant Lodge. The study’s statement of the problem revealed that, the decrease in revenue and escalation of operating expenses resulting in losses in the entity is a cause for concern since it has crippling the vision of the lodge of improving to a higher level. The researcher’s objectives outlined the financial management practices in use at Elephant Lodge, the financial management implementation guideline, challenges in implementing guidelines, personnel adequacy, controls and reviews of the financial management practices and the best practices. The descriptive survey research design was used and data was gathered through the use of structured questionnaires and interviews. From the findings, controls and reviews over the financial management policy have an effect on financial management practices and a system of sound controls can help ensure and improve the financial performance and improve the organisation’s profitability. The researcher provided recommendations on dealing with financial management practices such as employee participation in financial management policy formulation, promptly review their financial management policies, enhancement on financial reporting, accounting systems and information technology, staff training and development, strengthening internal control and shortening the cash conversion cycle.